Investment, Capital Accumulation, and Growth Some Evidence From the Gambia 1964-1998 - Beddies, Christian H. (International Monetary Fund, 1999)
This paper considers the potential variables that have determined economic growth in The Gambia during 1964-98. The results indicate that The Gambia's aggregate production function exhibits increasing returns to scale, thus supporting the endogenous growth-type model. The impact of private investment-and thus private capital accumulation-on output is large and significant. Furthermore, increases in public investment boost output substantially. Finally, the effects associated with human capital accumulation are positive and statistically significant. The paper also estimates a series on total factor productivity growth that indicates that The Gambia was able to use its resources more efficiently